RANCANG BANGUN SISTEM GPS TRACKER BERBASIS IRIDIUM SATELLITE NETWORK PADA DRIFTER UDAYANA - Praja Manggala, Nalendra; Dewi Wirastuti, Ni Made Ary Esta; Djuni Harta, I Gusti Agung Komang Diafari (Jurnal SPEKTRUM, 2025)
Science and technology continue to evolve every day, and their potential can be maximized to facilitate human work, including the needs of scientific research. Oceanographic data collection is a concrete example of technological utilization. Conventionally, data collection was done manually using human labor, but technological advancements have led to the creation of a device called a drifter. In oceanography, continuous and real-time data collection is essential for forecasting water conditions. Location and time data collection using the GPS UBLOX NEO 6M is utilized to obtain data on ocean current direction and speed. The RockBLOCK Mk2 9602 satellite-based communication module is used to avoid communication range limitations. A GPS Tracker system based on the Iridium Satellite Network has been successfully designed and built, and testing has been conducted to measure its ability to collect time and location data as well as its ability to transmit data using satellite communication. Testing was carried out by comparing GPS module data with data from Google Maps, as well as comparing data collected locally on an SD card with data collected on the Iridium server. comparing data collected locally on an SD card with data collected on the Iridium server. The research results show that the collected data has an average deviation of 0,36 meters.